The Power of Implicature in Addressing Covid19 as a Global Pandemic - Hassan, Ajyal; Jameel, Ali (Al-Adab Journal, 2023)
Since Covid19 is a contagious virus when infected, patients should follow the recommended instructions and precautions, the first was to stay isolated from the community as much as possible. (Public Health Agency of Sweden, 2020. Although social distancing has effectively resulted in slowing the virus’s spread, there are enormous challenges posed to societies to convince the public, especially in democratic countries, to stay-at-home at the essential outbreak (Engle et al. 2020; Fowler et al. 2020; Bilgin 2020; Abouk and Heydari 2020; Hale et al. 2020; Studdert and Hall 2020; Gostin and Hodge 2020). This study investigates the implied meanings in the speeches declaring COVID-19 a global pandemic and shedding light on associated ambiguity and implied meaning. To what extent was the hidden meaning in line with the strength and ambiguity of the Covid-19 epidemic? For the pragmatic analysis, which is qualitative and quantitative, the model is: flouting Grice’s maxims (1975) utilizing the off-record strategies of politeness by Brown and Levinson (1978, 1987), and the data understudy were two political speeches which were: The South African President Ramasopha and the Nigerian President Buhari’ speeches addressing Covid19 as a global pandemic. The results reveal the connection between implicature and many other factors that contribute to its existence and which are included in the context.